General and type 2 parvovirus‐specific passive immune transfer in puppies – Evaluation by early growth. (25th November 2018) - Mila, Hanna; Grellet, Aurélien; Feugier, Alexandre; Desario, Costantina; Decaro, Nicola; Buonavoglia, Canio; Mariani, Claire; Chastant‐Maillard, Sylvie
Contents: Failure of passive immune transfer put puppies at a higher risk of neonatal and weaning mortality due to low immune protection against infectious agents. The aim of this study was to investigate the evolution of the general via serum IgG concentration (IgG) and the specific via serum maternally derived canine parvovirus type 2‐specific antibody titer (CPV2 MDA) passive immune transfer within the first 4 weeks of age. Furthermore, the relationship between general and specific immune transfer and the possibility of non‐invasive evaluation was assessed. Puppies (169) were weighed systematically between birth and Day 28. IgG and CPV2 MDA were assayed in serum samples at 2 and at 28 days of age. At Day 2, there was a positive correlation between IgG and CPV2 MDA ( ρ = 0.71; p < 0.001). At Day 2, 17.9% (27/151) of puppies presented a deficit of passive immune transfer according to IgG result (defined as IgG < 2.3 g/L) and 25.8% (39/151) of puppies were under the minimal protective CPV2 MDA titer (defined as <1:160). No correlation between IgG and CPV2 MDA was observed at Day 28 ( ρ = 0.14; p = 0.11). Growth rate within the first 48 hours <−2.7% allowed to distinguish puppies at high risk of the general and specific passive immune failure (Youden's index = 0.79 and 0.75, respectively). The threshold value of early growth rate, although applicable only in puppies non‐supplemented with milk replacer, allows identifying via non‐invasive way individuals requiring a special care. Further investigation of the mechanism of passive immune transfer in dogs is necessary to understand the relationship between the general and specific immunoglobulin levels.